Comparative Analysis of RNA Virome Composition in Rabbits and Associated Ectoparasites - Mahar, Jackie E. (J Virol, 2020)
Ectoparasites play an important role in virus transmission among vertebrates. Little, however, is known about the nature of those viruses that pass between invertebrates and vertebrates. In Australia, flies and fleas support the mechanical transmission of two viral biological controls against wild rabbits—rabbit hemorrhagic disease virus (RHDV) and myxoma virus. We compared virome compositions in rabbits and these ectoparasites, sequencing total RNA from multiple tissues and gut contents of wild rabbits, fleas collected from these rabbits, and flies trapped sympatrically. Meta-transcriptomic analyses identified 50 novel viruses from multiple RNA virus families. Rabbits and their ectoparasites were characterized by markedly different viromes, with virus abundance greatest in flies. Although viral contigs from six virus families/groups were found in both rabbits and ectoparasites, they clustered in distinct host-dependent lineages. A novel calicivirus and a picornavirus detected in rabbit cecal content were vertebrate specific; the newly detected calicivirus was distinct from known rabbit caliciviruses, while the picornavirus clustered with sapeloviruses. Several picobirnaviruses were also identified that fell in diverse phylogenetic positions, compatible with the idea that they are associated with bacteria. Further comparative analysis revealed that the remaining viruses found in rabbits, and all those from ectoparasites, were likely associated with invertebrates, plants, and coinfecting endosymbionts. While no full genomes of vertebrate-associated viruses were detected in ectoparasites, small numbers of reads from rabbit astrovirus, RHDV, and other lagoviruses were present in flies. This supports a role for flies in the mechanical transmission of RHDV, while their involvement in astrovirus transmission merits additional exploration. IMPORTANCE Ectoparasites play an important role in the transmission of many vertebrate-infecting viruses, including Zika and dengue viruses. Although it is becoming increasingly clear that invertebrate species harbor substantial virus diversity, it is unclear how many of the viruses carried by invertebrates have the potential to infect vertebrate species. We used the European rabbit (Oryctolagus cuniculus) as a model species to compare virome compositions in a vertebrate host and known associated ectoparasite mechanical vectors, in this case, fleas and blowflies. In particular, we aimed to infer the extent of viral transfer between these distinct types of host. Our analysis revealed that despite extensive viral diversity in both rabbits and associated ectoparasites, and the close interaction of these vertebrate and invertebrate species, biological viral transmission from ectoparasites to vertebrate species is rare. We did, however, find evidence to support the idea of a role of blowflies in transmitting viruses without active replication in the insect.